MASLAHAH PEMBATASAN PERNIKAHAN DI TENGAH PANDEMI COVID-19 : (Studi di KUA Kec. Tiworo Tengah, Kab. Muna Barat) - Marwah, Siti (Sahaja: Journal Sharia and Humanities, 2022)
The Covid-19 pandemic in early 2020 began to spread in Indonesia. This resulted in the government having to issue policies, one of which was Large-Scale Social Restrictions (it called PSBB) which had an impact on various sectors of public life. Responding to this, the Director General of Islamic Community Guidance also issued a circular on Control of the Implementation of Marriage Services in the Emergency Period of Disease Outbreak due to Covid -19 which contains restrictions on the implementation and registration of marriage at the Religious Affairs Office. The decline in registration and restrictions on the implementation of marriage in every Religious Affairs Office decreased drastically, as was the case at the Central Tiworo Religious Affairs Office. Wedding restriction policy that occurred in the Religious Affairs Office at Middle Tiworo certainly have maslahah amid the pandemic Covid-19. This study aims to determine the problems in limiting marriage in the Central Tiworo District Office of Religious Affairs during the Covid-19 pandemic. Using method in this research is a qualitative method with the type of field research. The theory used is the maslahah theory according to Syatibi. The problem with limiting marriage in the middle of covid-19 is that it can break the chain of spreading covid-19, minimize the things that cause covid-19, and the costs of marriage that are spent are less because the number of attendees is limited.